Relationship between estimated glomerular filtration rate and severity of intracerebral hemorrhage - Kerinciani, Rani; Akbar, Muhammad; Sompa, Andi Weri; Massi, Muhammad Nasrum; Bahar, Ashari; Bintang, Andi Kurnia (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The effect of estimated glomerular filtration rate (eGFR) on intracerebral hemorrhage (ICH) severity is rarely studied. Meanwhile, the National Institute of Health Stroke Scale (NIHSS) is the gold standard scale for assessing stroke severity. Therefore, this study aimed to determine the relationship between eGFR and ICH severity. Methods: A cross-sectional study was conducted at Dr. Wahidin Sudirohusodo General Hospital. eGFR values were divided into 4 levels namely severe, moderate, mild, and normal, while the severity of stroke based on NIHSS was mild (<5), moderate (6–14), and severe (>15). Analysis to compare eGFR group values with NIHSS used chi-square analysis, and a p-value <0.05 was considered significant. Results: The results showed that the participants were mostly aged 45-70 years and male. Bleeding mostly occurred in the upper part of the brain (supratentorial) by 89.1%. The mean eGFR of participants was 84.65 mL/min/1.73 m² and the severity based on the NIHSS score ranged from 2-28. Furthermore, there was a significant relationship between eGFR values and NIHSS scores (p<0.001). Decreased eGFR tended to be associated with higher NIHSS indicated by a p-value of 0.018. Conclusions: Based on the results of this study, eGFR has a relationship with the severity of ICH.